The trajectory of anxiety and depressive symptoms and the impact of self-injury: A longitudinal 12-month cohort study of individuals with psychiatric symptoms. - Olivia Ojala; Maria Å Garke; Samir El Alaoui; David Forsström; Maria Hedman-Lagerlöf; Simon Jangard; Johan Lundin; Alexander Rozental; Shervin Shahnavaz; Karolina Sörman; Tobias Lundgren; Clara Hellner; et al. (PLoS ONE)
Background Individuals reporting self-injury are at greater risk of several adverse outcomes, including suicide. There is reason to be concerned how these individuals cope when stressful life events increase. This study aimed to investigate the trajectories of anxiety and depressive symptoms and the predictive value of self-injury history in individuals with psychiatric symptoms during the unique and stressful conditions of the COVID-19 pandemic. Methods In a longitudinal population cohort study (N = 1810) ranging from 2020 to 2022, anxiety (measured by Generalized Anxiety Disorder, GAD-7) and depressive symptoms (measured by Patient Health Questionnaire, PHQ-9) were self-reported monthly during 12 months. Latent growth curve models with and without self-reported self-injury history as predictors were conducted. Results Overall, anxiety and depressive symptoms decreased from baseline, but remained at moderate severity at follow-up. Individuals reporting suicidal or nonsuicidal self-injury reported significantly higher symptom severity at baseline. In addition, individuals reporting suicidal self-injury demonstrated a slower rate of decline in the symptom load over the course of 12 months. Conclusions Over the course of 12 months, anxiety and depressive symptoms decreased in individuals with psychiatric symptoms, but still indicate a psychiatric burden. Individuals with a history of self-injury could be more vulnerable in face of stressful conditions such as those experienced during the COVID-19 pandemic.